Dye‐Loaded Mechanochromic and pH‐Responsive Elastomeric Opal Films. Issue 1 (30th November 2020) - Winter, Tamara; Boehm, Anna; Presser, Volker; Gallei, Markus
Abstract: In this work, the preparation and fabrication of elastomeric opal films revealing reversible mechanochromic and pH‐responsive features are reported. The core–interlayer–shell (CIS) particles are synthesized via stepwise emulsion polymerization leading to hard core (polystyrene), crosslinked interlayer (poly(methyl methacrylate‐ co ‐allyl methacrylate), and soft poly(ethyl acrylate‐ co ‐butyl acrylate‐ co ‐(2‐hydroxyethyl) methacrylate) shell particles featuring a size of 294.9 ± 14.8 nm. This particle architecture enables the application of the melt‐shear organization technique leading to elastomeric opal films with orange, respectively, green brilliant reflection colors dependent on the angle of view. Moreover, the hydroxyl moieties as part of the particle shell are advantageously used for subsequent thermally induced crosslinking reactions enabling the preparation of reversibly tunable mechanochromic structural colors based on Bragg's law of diffraction. Additionally, the CIS particles can be loaded upon extrusion or chemically by a postfunctionalization strategy with organic dyes implying pH‐responsive features. This convenient protocol for preparing multi‐responsive, reversibly stretch‐tunable opal films is expected to enable a new material family for anti‐counterfeiting applications based on external triggers. Abstract : A convenient route for the preparation of multistimuli‐responsive dye‐loaded opal films is reported. By taking advantage of the powerful melt‐shear organization technique for hard core/soft shell particles featuring responsive dyes, new mechanochromic and pH‐responsive elastomeric opal films are fabricated showing fascinating structural colors. These combined properties result in a double safety attribute paving the way for anti‐counterfeiting materials.